Pro-Israel Product Boycotts: The Role of Influencers, Religiousity, and Brand Loyalty - Rahman, Farhan Taufik; Suryomukti, Wiku (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This paper presents an empirical investigation into the factors influencing consumer attitudes and actions regarding boycotts of Israeli products in the Jabodetabek region, focusing on the roles of influencers, religiousity, and brand loyalty. The study, conducted with a sample of 113 participants residing in Jabodetabek, employs purposive sampling to select respondents based on their relevance to the research objectives. The data were collected through an online questionnaire and analyzed using descriptive analysis and multiple linear regression in SPSS 22. The findings reveal that influencers and religiousity exert a significant positive influence on pro-Israel boycott actions, while brand loyalty has a significant negative impact. Moreover, this study have significant ramifications for developing more efficient approaches to enhance engagement in boycott actions, as well as for businesses comprehending the impact of influencers, religious values, and sustaining brand loyalty through high-quality products.